Laptev Sea System discussed at Russian-German workshop - Thiede, Jörn; Kassens, Heidemarie; Timokhov, Leonid (AGU (American Geophysical Union), 2000)
The fifth Laptev Sea System Project Workshop was held November 25-29,1999, at the State Research Center-Arctic and Antarctic Research Institute in St. Petersburg, Russia.The abstracts of the workshop have been published in Terra Nostra,Vol. 99 (11) by the Alfred Wegener Foundation, Cologne, Germany.